Crystal structure of poly[bis{μ2-5-carboxy-4′-methyl-[1,1′-biphenyl]-3-carboxylato-κ2O:O′}-{μ2-4,4′-bipyridine-κ2N:N′}]cobalt(II), C40H30N2O8Co - Hu Shao-Qiang; Li Shi-Hui (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C40H30N2O8Co, triclinic, P1̄ (no. 2), a = 9.8766(6) Å, b = 11.5473(8) Å, c = 14.2194(9) Å, α = 84.534(5)°, β = 85.582(5)°, γ = 79.413(5)°, V = 1583.90(17) Å3, Z = 2, Rgt(F) = 0.0650, wRref(F2) = 0.1109, T = 293(2) K.